Menggagas Sistem Ekonomi Alternatif (Upaya Mencari Kedudukan Ekonomi Islam) - Mashur Malaka (Institut Agama Islam Negeri (IAIN) Kendari, 2008)
What Paul A. Samuelson discloses in The Family of Economic which he calls The Main Stream of Economic, if we look further we will soon encounter a vacuum of economic thought from the first year of the AD until the discovery of ST. Tomas Aquinas in 1270 AD at that time interval according to